ASSESSMENT OF RISK ANALYSIS METHODS USING IN SECTOR BY USING CONTENT ANALYSIS - Yildirim, Ezgi; Yildirim, Esma Esin; Yildirim, Osman; Minga, Recep (STEF92 TECHNOLOGY LTD, 2014)
Occupational health and job safety is a crucial issue in modern global industrial life. This study aimed at investigating risk evaluation methods using in the sense of occupational health and job safety at industrial sectors by content analysis. The sector companies are examined according to hazard classes properties, the results are presented by frequency distributions. Additionally, assessment of risk analysis methods is reevaluated by occupational health and safety specialists who are certified by Work and Social Security Ministry in Turkey. Data analysis is done by content analysis.
Keywords: Occupational Health; Job Safety; Environmental concern; Content Analysis; SAFETY MANAGEMENT; Public, Environmental & Occupational Health; Sociology